KAP Study on Contraception in Teenage Pregnancy at Antenatal Care Clinic and Delivery Room in Chulalongkorn Memorial Hospital - Aurasa Hemachandra; Tassawan Rungruxsirivorn; Surasak Taneepanichskul; Kamthorn Pruksananonda (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective: To assess knowledge, attitude, and practice about contraception in pregnant teenagers.Materials and Methods: This was a cross-sectional descriptive study. Data collection started from September 2009 to March 2010. Pregnant teenagers, aged 12-19 years old, attending ANC clinic or delivery room at King Chulalongkorn Memorial Hospital were enrolled. The questionnaire consists of four parts; demographic data, contraceptive knowledge, attitudes about pregnancy and contraception, and past contraceptive practices. Data were analyzed using descriptive statistics, chi square test, t-test and Pearson correlation.Results: A total of 150 complete questionnaires from 285 cases of teenage pregnancy in this study period were collected and analyzed. The mean age of subjects was 17.7 years. Only 52.7% used any contraception at first intercourse. Contraceptive pill was the most common method used (59.5%) and only one-fourth chose condom. Up to 74% of participants were pregnant for the first time and 72% informed that their current pregnancies were unintended. The mean contraceptive knowledge score was 70.0 ± 9.7%. Their knowledge short-acting contraception was significantly more than long-acting contraception (P<.001). There was a correlation between knowledge and use of contraception at first intercourse (P=.012) and a trend of correlation between knowledge and attitude although not significant. Most of teenagers decided to use contraception by themselves. When they had any problems, only 19% went to see a doctor. Sources of contraceptive information were mainly from school teaching and mass media.Conclusion: Knowledge on contraception in pregnant teenagers was in average level. There was a correlation between knowledge and the use of contraception at first sexual intercourse. Most cases decided to use contraception themselves (63.5%). Pills was the most common contraceptive method (63.5%).